2002
DOI: 10.1074/jbc.m109739200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein-tyrosine Phosphatase Stimulates the Dynamin-dependent Endocytosis of ROMK1

Abstract: We have previously shown that inhibiting proteintyrosine kinase increased whereas inhibiting proteintyrosine phosphatase (PTP) decreased renal outer medullary potassium channel 1 (ROMK1) channel activity (1). We have now used confocal microscopy, the patch clamp technique, and biotin labeling to further examine the role of tyrosine phosphorylation in regulating ROMK1 trafficking. Human embryonic kidney 293 cells were cotransfected with c-Src and green fluorescent protein-ROMK1, which has the same biophysical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…In addition, overexpression of c-Src itself could mimic the effects of RTK activation, indicating that c-Src is not only necessary but also sufficient for BACE internalization. It is known that c-Src mediates internalization of membrane proteins by phosphorylating the internalized protein or components of the internalization machinery [20][21][22]24]. Our results suggest that in this case c-Src may phosphorylate components of the internalization machinery because no tyrosine residue was found in the cytosolic tail of BACE [16,21,23,24,62,63].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, overexpression of c-Src itself could mimic the effects of RTK activation, indicating that c-Src is not only necessary but also sufficient for BACE internalization. It is known that c-Src mediates internalization of membrane proteins by phosphorylating the internalized protein or components of the internalization machinery [20][21][22]24]. Our results suggest that in this case c-Src may phosphorylate components of the internalization machinery because no tyrosine residue was found in the cytosolic tail of BACE [16,21,23,24,62,63].…”
Section: Discussionmentioning
confidence: 58%
“…Upon activation, RTKs undergo phosporylation at specific tyrosine sites and then bind with SH2 (Src homology region) or PTB (phosphotyrosine binding) domain-containing proteins to activate downstream effectors such as c-Src, MAPK, and PKC [19]. Particularly, c-Src has been demonstrated to regulate the internalization of membrane proteins via different mechanisms [20][21][22][23][24], implicating a means for RTK-mediated regulation of other membrane proteins. RTK internalization is required for their normal signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Although both ROMK1 and ROMK2 transcripts are expressed in the CNT and CCD (9), only the ROMK1 isoform, which is exclusively expressed in these nephron segments, is regulated by PTK (31,32). PTK-stimulated endocytosis of ROMK1 in oocytes and HEK cells requires phosphorylation of the C-terminal consensus motif (Tyr-337 in ROMK1) (31). Because all ROMK iso- forms (1-3) have a C-terminal PTK phosphorylation motif, the reason for the isoform specificity of regulation by PTK likely involves the unique ROMK1 NH 2 terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis of romk channels is a dynamin-dependent process using clathrin-coated pits (30). Although both ROMK1 and ROMK2 transcripts are expressed in the CNT and CCD (9), only the ROMK1 isoform, which is exclusively expressed in these nephron segments, is regulated by PTK (31,32). PTK-stimulated endocytosis of ROMK1 in oocytes and HEK cells requires phosphorylation of the C-terminal consensus motif (Tyr-337 in ROMK1) (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, the stimulatory effect of SGK1 on WNK4's phosphorylation was absent in the presence of high SFK activity (12). A large body of evidence has demonstrated that SFK plays an important role in inhibiting ROMK channels in the CCD (24)(25)(26)(27)(28)(29). We have previously demonstrated that SFK phosphorylates the ROMK1 channel at Tyr 337 (14) thereby facilitating internalization of ROMK channels (24).…”
Section: Ptp-1d Interacts With Wnk4 Via Tyr 1143 To Reduce the Inhibimentioning
confidence: 99%